2023
DOI: 10.1177/02698811231154852
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin-assisted therapy for major depressive disorder: An exploratory placebo-controlled, fixed-order trial

Abstract: Background: Several early phase studies have demonstrated that psilocybin-assisted therapy has rapid-acting and persisting antidepressant effects from just one or two doses. However, methodological limitations (e.g., placebo-control, blinding) limit interpretability of the existing literature. Methods: In an exploratory placebo-controlled, within-subject, fixed-order study, individuals with moderate to severe major depressive disorder were administered placebo ( n = 19) followed by psilocybin (0.3 mg/kg) ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…Through the review of their references, 20 additional articles were identified. After excluding ineligible articles and secondary analysis, 36 articles were identified for inclusion in this systematic review (Anderson et al, 2020; Bogenschutz et al, 2015, 2022; Bouso et al, 2008; Carhart-Harris et al, 2016, 2021; Danforth et al, 2018; Davis et al, 2021; Gasser et al, 2014; Goodwin et al, 2022; Griffiths et al, 2016; Grob et al, 2011; Grof et al, 1973, 1972; Holze et al, 2022; Johnson et al, 2014; Kast, 1967; Kurland et al, 1971; Mccabe et al, 1972; Mitchell et al, 2021; Mithoefer et al, 2011, 2018; Monson et al, 2020; Moreno et al, 2006; Oehen et al, 2013; Osorio et al, 2015; Ot’alora et al, 2018; Pahnke et al, 1969; Palhano-Fontes et al, 2019; Richards et al, 1977; Ross et al, 2016; Sanches et al, 2016; Savage and McCabe, 1973; Schneier et al, 2023; Sloshower et al, 2023; Wolfson et al, 2020). A PRISMA flow diagram of our systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the review of their references, 20 additional articles were identified. After excluding ineligible articles and secondary analysis, 36 articles were identified for inclusion in this systematic review (Anderson et al, 2020; Bogenschutz et al, 2015, 2022; Bouso et al, 2008; Carhart-Harris et al, 2016, 2021; Danforth et al, 2018; Davis et al, 2021; Gasser et al, 2014; Goodwin et al, 2022; Griffiths et al, 2016; Grob et al, 2011; Grof et al, 1973, 1972; Holze et al, 2022; Johnson et al, 2014; Kast, 1967; Kurland et al, 1971; Mccabe et al, 1972; Mitchell et al, 2021; Mithoefer et al, 2011, 2018; Monson et al, 2020; Moreno et al, 2006; Oehen et al, 2013; Osorio et al, 2015; Ot’alora et al, 2018; Pahnke et al, 1969; Palhano-Fontes et al, 2019; Richards et al, 1977; Ross et al, 2016; Sanches et al, 2016; Savage and McCabe, 1973; Schneier et al, 2023; Sloshower et al, 2023; Wolfson et al, 2020). A PRISMA flow diagram of our systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the identified studies used psilocybin (Anderson et al, 2020; Bogenschutz et al, 2015, 2022; Carhart-Harris et al, 2016, 2021; Davis et al, 2021; Goodwin et al, 2022; Griffiths et al, 2016; Grob et al, 2011; Johnson et al, 2014; Moreno et al, 2006; Ross et al, 2016; Schneier et al, 2023; Sloshower et al, 2023), nine used MDMA (Bouso et al, 2008; Danforth et al, 2018; Mitchell et al, 2021; Mithoefer et al, 2011, 2018; Monson et al, 2020; Oehen et al, 2013; Ot’alora et al, 2018; Wolfson et al, 2020), eight used LSD (Gasser et al, 2014; Grof et al, 1972; Holze et al, 2022; Kast, 1967; Kurland et al, 1971; Mccabe et al, 1972; Pahnke et al, 1969; Savage and McCabe, 1973), three used ayahuasca (Osorio et al, 2015; Palhano-Fontes et al, 2019; Sanches et al, 2016) and three used DPT (Grof et al, 1972, 1973; Richards et al, 1977). No article using DMT, mescaline or ibogaine met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The breaking blind problem is therefore the rule rather than the exception in psychedelic trials (Muthukumaraswamy et al, 2021). For instance, in a recently published placebo-controlled study, 15 of 19 participants correctly guessed they had received a placebo, while 12 of 15 participants correctly guessed they receive an active dose after a medium-to high-dose psilocybin session (Sloshower et al, 2023; unfortunately they did not report the clinicians' guesses about treatment allocation). This threatens internal validity and the conclusions that can be drawn based on clinical studies for several reasons.…”
Section: The Breaking Blind Problemmentioning
confidence: 99%
“…In summary, our review of the literature on the efficacy of psilocybin-assisted treatments for psychiatric disorders and SUDs points to mixed results with early promise for certain disorder types. The strongest efficacy data until now is for psilocybinassisted treatment in the depression and anxiety disorders (Agin-Liebes et al, 2020;Sloshower et al, 2023;Thomas et al, 2017). However, interpreting this data is complicated by the lack of good placebo conditions for hallucinogen-based treatments and problems with generalizability of study populations for depression/anxiety RCTs, half of which were conducted in patients with end-of-life cancer diagnoses (Thomas et al, 2017).…”
Section: Summary Of Efficacy Data For Psilocybinassisted Treatmentsmentioning
confidence: 99%